Mechanical properties of hyaline and repair cartilage studied by nanoindentation - Franke, Oliver; Durst, Karsten; Maier, Verena; Göken, Mathias; Birkholz, Torsten; Schneider, Holm; Hennig, Friedrich; Gelse, Kolja (Acta Biomaterialia, 2007)
Articular cartilage is a highly organized tissue that is well adapted to the functional demands in joints but difficult to replicate via tissue engineering or regeneration. Its viscoelastic properties allow cartilage to adapt to both slow and rapid mechanical loading. Several cartilage repair strategies that aim to restore tissue and protect it from further degeneration have been introduced. The key to their success is the quality of the newly formed tissue. In this study, periosteal cells loaded on a scaffold were used to repair large partial-thickness cartilage defects in the knee joint of miniature pigs. The repair cartilage was analyzed 26 weeks after surgery and compared both morphologically and mechanically with healthy hyaline cartilage. Contact stiffness, reduced modulus and hardness as key mechanical properties were examined in vitro by nanoindentation in phosphate-buffered saline at room temperature. In addition, the influence of tissue fixation with paraformaldehyde on the biomechanical properties was investigated. Although the repair process resulted in the formation of a stable fibrocartilaginous tissue, its contact stiffness was lower than that of hyaline cartilage by a factor of 10. Fixation with paraformaldehyde significantly increased the stiffness of cartilaginous tissue by one order of magnitude, and therefore, should not be used when studying biomechanical properties of cartilage. Our study suggests a sensitive method for measuring the contact stiffness of articular cartilage and demonstrates the importance of mechanical analysis for proper evaluation of the success of cartilage repair strategies.
Created from Fastlane, Scopus look-up
Keywords: Cartilage; Nanoindentation; Soft tissues; Stiffness; Storage effect